Modelling elements of microstructure in olivine - Breithaupt, T (2022)
To solve problems in the Earth and planetary sciences ranging from mantle convection and plate tectonics, magma dynamics, glacial-isostatic adjustment, post-seismic creep, seismic attenuation, and tidal dissipation, we require a deep understanding of the rheological, seismic, and chemical properties of silicate materials. Elements of microstructure, such as grain size and dislocation density, exert a strong control on these properties. In this thesis, I apply novel approaches to modelling the time evolution of these quantities.